2016
DOI: 10.1007/s13201-016-0385-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of combined toxicity of heavy metals from industrial wastewaters on Photobacterium phosphoreum T3S

Abstract: This research work is focusing on the toxicities of heavy metals of industrial origin to anaerobic digestion of the industrial wastewater. Photobacterium phosphoreum T3S was used as an indicator organism. The acute toxicities of heavy metals on P. phosphoreum T3S were assessed during 15-min half inhibitory concentration (IC50) as indicator at pH 5.5-6. Toxicity assays involved the assessment of multicomponent mixtures using TU and MTI approaches. The results of individual toxicity indicated that the toxicity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
2
13
0
1
Order By: Relevance
“…One possible explanation is that these metals concentrations are less than their EC50 (Zeb et al 2016); in addition, the combined TPH concentration in these soil samples was very low (25 mg kg -1 ). number of copies of the alkB gene, the gene of interest in this study, in comparison to soil samples with lower TPH concentration (Table 3).…”
Section: Soil and Contaminants Characterisationmentioning
confidence: 88%
See 1 more Smart Citation
“…One possible explanation is that these metals concentrations are less than their EC50 (Zeb et al 2016); in addition, the combined TPH concentration in these soil samples was very low (25 mg kg -1 ). number of copies of the alkB gene, the gene of interest in this study, in comparison to soil samples with lower TPH concentration (Table 3).…”
Section: Soil and Contaminants Characterisationmentioning
confidence: 88%
“…The most dominant factor regarding the toxicity was the presence of Pb; elevated toxicity was observed in samples with a relatively high concentration of Pb. A previous study (Zeb et al 2016) showed that the toxicity of Pb, as a single contaminant, was 0.046 TU for V. fischeri. However, in this study Pb showed a much higher level of toxicity as it is combined with other contaminants.…”
Section: Soil and Contaminants Characterisationmentioning
confidence: 95%
“…Standard procedure was adopted to prepare metal stock solutions ranging over (0.5, 1, 10, 100 and 1000 ppm or mg/L) by dissolving the AAS grade metal in deionized water. The solutions were freshly prepared [ 13 ]. Ten concentrations of the tested metals were prepared from stock solutions to carry out a preliminary experiment in triplicate to determine the suitable metal concentration array for determining the half maximal inhibitory concentration IC 50 of each tested metal.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, the analysis of the total amount of heavy metals is unable to represent the full environmental behaviors and ecological effects of heavy metals [ 11 ]. Numerous studies deal with risk effects of single metal types, while in reality the aquatic organisms are often exposed to mixtures of metals [ 12 , 13 ]. Thus, the effects of co-existing multiple chemicals cannot be ignored and interactions of components in a mixture might cause significant changes in the properties of its constituents [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Relative luminescence unit (RLU) was obtained by expression (1), which was developed by mean luminosity unit of test samples (LU) and blank controls (LU 0 ) (Zeb et al, 2017). The luminescence inhibition ratio (I%) was calculated by expression (2) to evaluate the effect of different concentrations of OTA on P. leiognathi at each time point (Bosch-Orea et al, 2017).…”
Section: Detection Of Ota Toxicitymentioning
confidence: 99%